Endoscope-Assisted Retrosigmoid Approach for Vestibular Schwannomas With Intracanalicular Extensions: Facial Nerve Outcomes - Bi, Yunke; Ni, Yunjia; Gao, Dandan; Zhu, Qingwei; Zhou, Qiangyi; Tang, Junjia; Liu, Juan; Shi, Fei; Li, Hongchan; Yin, Jian; Liu, Yaohua; Lou, Meiqing (Frontiers in Oncology, 2022)
Objective: To explore the role of neuroendoscope assistance during surgical resection of the intracanalicular portion of vestibular schwannomas via the retrosigmoid approach and the subsequent early facial nerve outcomes. Methods: Patients of vestibular schwannoma with intracanalicular extensions undergoing retrosigmoid dissection at a single institution were retrospectively analyzed in this study. Several surgical techniques were applied to ensure maximal and safe removal of tumors. Tumors extending less than 10 mm into the internal acoustic canal (IAC) were classified as Grade A, while those extending over 10 mm into IAC were taken as Grade B. Neuroendoscope was applied at the end of microscopic phase to search for potential remnants for Grade B tumors. Absolute tumor extension was defined and measured. House and Brackmann (HB) scale was used to evaluate immediate CN VII outcomes. Results: Of the 61 patients, there were 38 females and 23 males. 18 (29.51%) cases were Koos Grade II, 12 (19.67%) cases Koos Grade III, 31 (50.82%) cases Koos Grade IV. There were 38 cases (62.30%) of Grade A and 23 cases (37.70%) of Grade B. Gross total resection was achieved in 60 cases (98.36%). 4 cases of intracanalicular remnants were detected and completely removed under endoscopic visualizations. There was a significantly higher proportion (17%, p = 0.02) of intracanalicular remnants in Grade B than Grade A. CN VII and VIII were anatomically preserved in all cases. 55 cases (90.16%) retained good (HB Grade 1 and 2) facial nerve outcomes. Conclusions: In Grade B vestibular schwannomas, after maximal microsurgical removal, endoscopic evaluation of the intracanalicular portion revealed residual tumors in 17% of the patients. Hence endoscopic evaluation of the potential intracanalicular remnants for tumor extending over 10 mm within IAC (Grade B) is recommended.